Childhood asthma complications, management, and environmental triggers - Alzamzami, Abdulghani A.; Alenezi, Seeta S.; Saptan, Laila M.; Alkaki, Renad T.; Albaqami, Shada M.; Karbouji, Rayan A.; Daba, Weam F.; Alahmadi, Raed A.; Hafez, Ahmad M.; Asiri, Hussain A.; Alhabshi, Nawaf H. (International Journal Of Community Medicine And Public Health, 2023)
Childhood asthma, which is a chronic respiratory condition, presents challenges in terms of its complications, management, and identification of environmental triggers. This review of existing literature explores the complexities surrounding asthma. It delves into complications, strategies for managing the condition, and the crucial role that environmental factors play in worsening it. Uncontrolled asthma in children has far-reaching consequences as it affects lung function, physical activity levels, and overall quality of life. Early recognition and addressing of these complications are essential to minimize long-term effects. The management of childhood asthma has evolved to focus on treatment plans, with corticosteroids being a key component. For cases, advanced therapeutic options like biologics are available. Indoor and outdoor environmental triggers have an impact on asthma exacerbations, making targeted preventive measures necessary. Education plays a role by providing caregivers and children with asthma action plans as well as proper inhaler technique guidance. Regular follow-up visits ensure assessment and adjustment of treatment plans while fostering a relationship between healthcare providers and families. Comprehensive care for childhood asthma involves an approach that includes pediatricians, pulmonologists, allergists, and respiratory therapists. The triad of interventions, environmental modifications, and educational strategies forms an encompassing framework for the management of asthma. This review highlights how crucial it is to tackle childhood asthma issues. By doing so, we can improve outcomes. Promote the overall well-being of children who are affected by this condition.